The Ambiguity of Chinese Joke "Xiehouyu": A Research Based on Sigmund Freud's Joke Theories - Qin, Sifei (Litera, 2019)
This article analyzes Xiehouyu - a kind of Chinese proverb created by Chinese working people since ancient times. Xiehouyu consists of two parts. The former segment serves as a riddle for the addressee, the latter part acts as the answer. One would often only state the first part, expecting the addressee to grasp the true meaning of the sentence by himself.
CRIS-Team WoS Importer:2020-01-10